Web crippling studies of SupaCee sections under two flange load cases. (15th December 2017) - Sundararajah, Lavan; Mahendran, Mahen; Keerthan, Poologanathan
Highlights: Experimentally investigated the web crippling of SupaCee sections under ETF and ITF load cases. Suitable finite element models were developed and validated using test results. Current web crippling design rules in AS/NZS 4600 and AISI S100 are inadequate for SupaCee sections. Proposed improved design equations based on test and finite element analysis results. Suitable design equations were also developed under the direct strength method. Abstract: Cold-formed steel channel sections are generally used as flexural members in light weight steel construction. Improved channel section profiles such as SupaCee sections with longitudinal web stiffeners and curved lips are also used instead of the conventional lipped channel sections. Web crippling capacities of these innovative sections can be different from those of conventional lipped channel sections. However, the web crippling behaviour and strength of these high strength SupaCee sections has not been investigated yet. Current web crippling design methods given in cold-formed steel design standards do not include any design procedures for SupaCee sections. Hence an experimental study involving 36 web crippling tests was first undertaken to investigate the web crippling behaviour and strengths of SupaCee sections under two flange load cases with their flanges unfastened to the supports. Comparison of experimental results showed that the web crippling capacities of SupaCee sections are reduced in comparison to lipped channel sections. Therefore the current web crippling design equations in the American and Australian/New Zealand cold-formed steel design standards were modified by including suitable web crippling coefficients for SupeCee sections. Finite element models of tested SupaCee sections were also developed and validated using the experimental results. This paper presents the details of the experimental and numerical web crippling studies of SupaCee sections under two flange load cases and the results. It also presents the details of direct strength method based design equations developed in this research.